Detection of 2,4,6-Trinitrotoluene by MIP-composite Based Electrochemical Sensor - Tasawan Puttasakul; Chompoonuch Tancharoen; Wannisa Sukjee; Chuchart Pintavirooj; Chak Sangma (My University, 2021)
In Thailand, there are terrorist groups active in some areas where casualties from their operations are civilians. Most of these casualties are from explosive device. The main component of the device is high explosive compound called 2,4,6-trinitrotoluene (TNT). Detection of TNT from objects and places in the suspected or area bombardment will provide useful evidence for the authority. In this work, we fabricate an electrochemical TNT sensor based on molecularly imprinted polymers (MIP) nanocomposites. The sensor aimed at TNT trace detection from solution of solid specimens. The sensor was able to detect TNT in solution with 3 log-scale linearity with 0.4 ppt lower limit of detection. The selectivity of the sensor toward TNT was considerably high compared with the other nitro compound.
Keywords: Luminescence and Fluorescent Materials; Molecular Sensors and Ion Detection; Mass Spectrometry Techniques and Applications